PEMANFAATAN BOKASHI FESES SAPI TERHADAP PRODUKTIVITAS RATUN SORGUM VARIETAS KAWALI - Wantania, Delty Indhira; Rumambi, A.; Kaunang, W.B (Universitas Sam Ratulangi, 2018)
UTILIZATION OF BOKASHI FESES COW ON PRODUCTIVITY RATOON OF KAWALI SORGHUM VARIETY. This study aims to determine the effect of bokashi cow feces on the productivity of ratoon sorghum variety of kawali. This research was implemented in Wusa village at districts Talawaan. The design used was completely randomized design (CRD), which consists of 4 treatments and 5 replications to obtain 20 units of trial. The treatment consists of P0= without fertilization, P1= 4 kg of fertilization, P2= 8 kg of fertilization, P3= 12 kg of fertilization.Â The measured variables are number of tillers, plant height, and panicle weight. Result of the analysis showed that treatment with 12 kg/plot provides highly significant effect (P <0.01) of the number of tillers, plant height, and panicle weight compared with other treatments, ie 8 and 4 kg/plot. The HSD test indicated that treatment number of tillers showed that between treatment P3, P0, P1, and P2 showed highly significant. In the treatments of advanced test HSD indicated also that plant height between P3, P0, P1, and P2 showed highly significant. In the treatment of panicle weight of advanced test of HSD showed that between treatment P3 and P0, treatment of P3 and P1 is very different, but the treatment of P3 and P2 showed no significant difference. Based on this research it can be concluded that cattle feces bokashi as the organic fertilizer up to 12 kg produced the best effect on number of tillers, plant height, and panicle weight.Â Keywords: Bokashi, productivity, ratoon, sorghum, kawali